Factors Influencing the Success of Early Initiation of Breastfeeding (IMD) in Postpartum Mothers - Yumi Abimulyani; Nelly Mariati (Oshada, 2025)
Early Initiation of Breastfeeding (IMD) is an important intervention that supports newborn survival and maternal health, especially in the first hour of life. IMD can prevent around 22% of neonatal deaths and provides benefits in the form of improving the baby's immune system through colostrum and stabilizing the baby's body temperature. In addition, IMD is also beneficial for the mother, such as accelerating uterine involution and supporting the formation of emotional bonds between mother and baby. Although the benefits are very significant, the implementation of IMD in the field still faces various challenges, such as lack of understanding of health workers, limited facilities, and policies that do not provide optimal support, especially for cesarean deliveries. In Indonesia, the low coverage of IMD reflects the gap between national health policies and their implementation in the field, with only 58.2% of babies receiving IMD. Factors that influence the success of IMD include the mother's level of knowledge, mental readiness, and support from competent health workers. This study uses a descriptive qualitative approach to describe the factors that influence the success of IMD in postpartum mothers. The results of the study are expected to provide recommendations for improving policies and practices of maternal and child health services, as well as expanding the coverage of IMD in Indonesia